Boiling Heat Transfer Characteristics of Noah-2100A and HFE-649 in Pin-Fin Microchannel Heat Sink - Hanying Jiang; Xiucong Zhao; Meng Zhang (Energies)
Noah-2100A and HFE-649, as two electronics fluorinated liquids (EFLs) with low saturation temperature, high safety, excellent insulation properties, and low environmental impact, are considered as replacements for the refrigerants with high Global Warming Potential (GWP), such as HFC-134a and HFC-245fa, in electronic cooling system. However, there is still a knowledge gap of boiling heat transfer for these two EFLs, especially in pin-fin microchannel. The effect of inlet temperatures, mass flow rates, and inlet vapor qualities on boiling heat transfer for two EFLs were studied experimentally in this paper. Overall, though the Noah-2100 has a higher pressure drop-in microchannel than HFE-649, Noah-2100A shows a higher overall thermal performance than HFE-649. Newly developed correlations of the Nusselt number (Nu) and pressure drop for two EFLs in a pin-fin microchannel heat sink were also presented. The proposed correlations can achieve a 10% and 11% mean average percentage error for Nu number and pressure drop.